2017
DOI: 10.1108/jd-01-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Representation of indigenous cultures: considering the Hawaiian hula

Abstract: Purpose The purpose of this paper is to explore the representation of Kanaka Maoli (Hawaiian) Hula Dance in traditional systems of representation and organization. Design/methodology/approach This exploratory study analyzes the controlled and natural language vocabularies employed for the representation and organization of Hawaiian culture, in particular Hawaiian hula. The most widely accepted and used systems were examined: classification systems (Library of Congress Classification and Dewey Decimal Classif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Patrick Wilson explains the professional role is an outcome of education, traditions of the profession, its ideas, and expectations 15 . But the researchers of academic librarians related their roles to their work tasks, information services function and status 16 . Sometimes the functions in this context are understood widely, e.g., as educational, cultural, research, recreational, informational, and bibliographic, but sometimes they are as narrow as providing library services 17 , managing a collection or training information literacy skills 18 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patrick Wilson explains the professional role is an outcome of education, traditions of the profession, its ideas, and expectations 15 . But the researchers of academic librarians related their roles to their work tasks, information services function and status 16 . Sometimes the functions in this context are understood widely, e.g., as educational, cultural, research, recreational, informational, and bibliographic, but sometimes they are as narrow as providing library services 17 , managing a collection or training information literacy skills 18 .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is a growing body of literature on indigenous knowledge organization (Adler, 2016; Duarte & Belarde‐Lewis, 2015; Doyle, 2013; Green, 2015; Lilley, 2015; Littletree & Metoyer, 2015; Lee, 2011; Montenegro, 2019; Hajibayova, Buente, Quiroga, & Valeho‐Novikoff, 2016; Hajibayova & Buente, 2017; Kam, 2007; Webster & Doyle, 2008). Green (2015) argues that the complicated relationship between mainstream perspectives and indigenous perspectives are difficult to untangled, resulting in KOS such as DDC to be misunderstood or truly biased.…”
Section: Related Workmentioning
confidence: 99%
“…Green (2015) argues that the complicated relationship between mainstream perspectives and indigenous perspectives are difficult to untangled, resulting in KOS such as DDC to be misunderstood or truly biased. Despite efforts in expanding DDC as described in Green (2015), how mainstream KOS such as LCSH, DCC, or the Library of Congress Classifications (LCC) can be skewed in describing minority groups have been manifested in Hajibayova et al (2016) and Hajibayova and Buente (2017). The authors investigate the topic of Hawaiian Hula and found that these KOS depict Hula dance as a strand of folk dance, rather than what indigenous peoples consider to be a “sacred celebration.”…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Cataloging practices that physically place tribal creation stories next to fairy tales rather than with other world religions reflects prejudiced structures in library practices (Kostelecky et al, 2017). This problematic classification and organization of library resources further embeds misinformation about Indigenous peoples, history, and culture within libraries (Aase, 2017;Hajibayova & Buente, 2017).…”
Section: Indigenous Knowledgementioning
confidence: 99%